2021
DOI: 10.3390/agronomy11102048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genotype and Climatic Conditions on the Oil Content and Its Fatty Acids Composition of Carthamus tinctorius L. Seeds

Abstract: Safflower seeds provide an oil rich in mono and polyunsaturated fatty acids. Its adaptation to drought and high temperatures makes it an alternative for the development of oleaginous crops in semi-arid areas. This study examines the oil content and the chemical composition of seed oil from three safflower accessions (Gila, Halab, Touggourt) cultivated over three years (2015, 2016, and 2017) in a semi-arid area in Tiaret (West of Algeria). Under these semi-arid conditions, characterized by low rainfall and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…1). As already reported in literature, temperatures and rainfall have an important impact on fatty acid composition in several oilseed species (Gouzy et al, 2016;Roche et al, 2016Roche et al, , 2019Merah et al, 2020;Nguyen et al, 2020;Zemour et al, 2021). In Atlas Pistachio, Labdelli et al (2019) reported differences in oil content and fatty acid composition in four locations.…”
Section: Fatty Acid Compositionsupporting
confidence: 55%
See 1 more Smart Citation
“…1). As already reported in literature, temperatures and rainfall have an important impact on fatty acid composition in several oilseed species (Gouzy et al, 2016;Roche et al, 2016Roche et al, , 2019Merah et al, 2020;Nguyen et al, 2020;Zemour et al, 2021). In Atlas Pistachio, Labdelli et al (2019) reported differences in oil content and fatty acid composition in four locations.…”
Section: Fatty Acid Compositionsupporting
confidence: 55%
“…Our reports have studied the chemical composition of different oil crops species as Brassicaceae (rapeseed and woad), shell seeds (sunflower and safflower) and oleoproteaginous and mucilaginous seeds (flax, camelina; Roche et al, 2010a, 2010b: Fabre et al, 2015, 2020: Zemour et al, 2021: Cassen et al, 2022. In a first publication, we studied the accumulation of oil and both fatty acid and sterols composition during seed development and filling of chia (Gravé et al, 2019).…”
mentioning
confidence: 99%
“…In particular, the analysis of the lipid composition of different cardoon plant tissues verified the higher lipid content in samples collected at intermediate stages of maturation, e.g., samples of bracts at PGS 5/6 [20], floral capitula at PGS 5 [13], and petioles at PGS 6/7 [14]. Similar results were reported by Curt et al [21], who also noted the significant effect of the growing condition on the fatty acid composition of cardoon seed oil, as well by Ashrafi and Razmjoo [22] and Zemour et al [23], who studied the fatty acid composition of safflower seeds. According to Sanyal and Linder [24], the proportion of saturated and unsaturated fatty acids is adapted according to the ambient temperatures to increase fitness as part of plants' adaptive evolution.…”
Section: Lipidic Fraction and Fatty Acids' Compositionsupporting
confidence: 83%
“…Despite this potential for producing desirable bioproducts, the yield of fatty acids from T. fusca cultures is relatively low as compared to such oleaginous organisms, such as plant oil seed crops (e.g., sunflower, canola, safflower), yeasts (e.g., Yarrowia lipolytica and Rhodosporidium toruloides ) and microalgae (e.g., Botryococcus braunii ). These later organisms hyperaccumulate fatty acid containing neutral lipids that can account for 20–60% of the dry biomass ( Banerjee et al, 2002 ; Sharafi et al, 2015 ; Patel et al, 2019 ; Liu H. et al, 2021 ; Liu Y. et al, 2021 ; Petraru et al, 2021 ; Zemour et al, 2021 ). In contrast, T. fusca accumulates fatty acids at approximately 1 mg/g dry biomass.…”
Section: Discussionmentioning
confidence: 99%